Marine-Inspired Ovothiol Analogs Inhibit Membrane-Bound Gamma-Glutamyl-Transpeptidase and Modulate Reactive Oxygen Species and Glutathione Levels in Human Leukemic Cells - Zuccarotto, Annalisa; Russo, Maria; Di Giacomo, Annamaria; Casale, Alessandra; Mitric, Aleksandra; Leone, Serena; Russo, Gian Luigi; Castellano, Immacolata (Marine Drugs, 2025)
The enzyme γ-glutamyl transpeptidase (GGT), located on the surface of cellular membranes, hydrolyzes extracellular glutathione (GSH) to guarantee the recycling of cysteine and maintain intracellular redox homeostasis. High expression levels of GGT on tumor cells are associated with increased cell proliferation and resistance against chemotherapy. Therefore, GGT inhibitors have potential as adjuvants in treating GGT-positive tumors; however, most have been abandoned during clinical trials due to toxicity. Recent studies indicate marine-derived ovothiols as more potent non-competitive GGT inhibitors, inducing a mixed cell-death phenotype of apoptosis and autophagy in GGT-overexpressing cell lines, such as the chronic B leukemic cell HG-3, while displaying no toxicity towards non-proliferative cells. In this work, we characterize the activity of two synthetic ovothiol analogs, L-5-sulfanylhistidine and iso-ovothiol A, in GGT-positive cells, such as HG-3 and HL-60 cells derived from acute promyelocytic leukemia. The two compounds inhibit the activity of membrane-bound GGT, without altering cell vitality nor inducing cytotoxic autophagy in HG-3 cells. We provide evidence that a portion of L-5-sulfanylhistidine enters HG-3 cells and acts as a redox regulator, contributing to the increase in intracellular GSH. On the other hand, ovothiol A, which is mostly sequestered by external membrane-bound GGT, induces intracellular ROS increase and the consequent autophagic pathways. These findings provide the basis for developing ovothiol derivatives as adjuvants in treating GGT-positive tumors’ chemoresistance.
CRIS-Team Scopus Importer:2025-09-19
Keywords: 5-thiohistidine; gamma-glutamyl-transpeptidase; GGT inhibitors; glutathione; leukemic cells; ovothiols